Fouling studies of colloidal, organic and their mixtures on RO membranes - Koh, Jia Le (2017)
This report examines the fouling characteristics of four different combinations of fouling process on reverse osmosis membranes. These combinations include colloidal fouling, organic fouling, mixed fouling with 20ppm of humic acid and mixed fouling with 30ppm of humic acid. Theoretical studies have shown that colloidal and organic fouling made up the majority of foulants present in water and wastewater treatment and these foulants can cause potential adverse effects in reverse osmosis performance. The experimental results have shown that the increase in trans-membrane pressure of mixed fouling was 10-16%, which was almost doubled that of colloidal fouling (5%) and organic fouling (9%). This result can be attributed to the concepts of cake formation and cake enhanced osmotic pressure caused by colloidal silica and humic acid. Analysis tests have also been conducted on membrane samples that underwent the abovementioned fouling experiments. Total organic carbon analysis results have shown that the middle segment of the membrane generally contains the highest amount of organic carbon and the results from Inductively Coupled Plasma analysis were consistent for both mixed fouling experiments. Scanning electron microscopy imaging was also performed to analyse the structure of the fouling layer on membrane surface. The results showed that colloidal fouling has a systematic arrangement of colloids and rather even across the membrane surface; organic fouling depicts humic lumps were uneven across the membrane surface; and mixed fouling showed that the humic lumps adhered to colloidal silica randomly across the membrane surface. However, ultrasonic time domain reflectometry analysis did not yield any results. This is probably due to the fact that the fouling layer on the membrane surface is not significant enough to be read by the time domain oscilloscope. Nevertheless, the present investigation shows that mixed fouling can cause higher adverse effects than colloidal fouling and organic fouling alone.